Aggressive humor style and cyberbullying perpetration: Normative tolerance and moral disengagement perspective - Zhu, Hong; Ou, Yilin; Zhu, Zimeng (Frontiers in Psychology, 2022)
The literature has acknowledged the correlation between aggressive humor style and cyberbullying perpetration; however, little is known about how this occurs. In this study, we sought to gain an understanding of how and when someone with an aggressive humor style may develop into a perpetrator of cyberbullying. We propose that whether an individual’s aggressive humor style results in cyberbullying perpetration depends on online social norms of tolerance for aggressive humor. When online normative tolerance for aggressive humor is high, individuals’ aggressive humor style is positively correlated with their moral disengagement, which, in turn, increases their intention to commit cyberbullying. When online normative tolerance for aggressive humor is low, the effect of individuals’ aggressive humor style on their moral disengagement is attenuated, which, in turn, weakens the relationship between aggressive humor style and cyberbullying perpetration. A total of 305 Chinese university students were recruited to participate in the experiment, and we found support for this hypothesis across the experiment. Several theoretical and practical implications are discussed.